Last resort [videorecording (DVD)] - Mineo, Jean-Marc; Foo, Jon; Norcross, Clayton; Ismalone, David (Shoreline Entertainment, 2025)
Jon Foo stars as a former special forces operative who turns a luxury resort into a war zone when mercenaries kidnap his family during a deadly bank heist. This martial arts action thriller delivers hand-to-hand combat, explosive gunfights, and a ticking-clock mission to stop a global bioterror plot.